The Current State of Implementation of the Research Management System of the National University of Laos - Vannasouk Bouasangthong; Khamseng Thalangsy; Intong Leusinxay (MASI Mandiri Edukasi, 2025)
The study examined the current implementation of the research management system at the National University of Laos. The population comprised 1,302 faculty members across 13 affiliated faculties, with a sample size of 306 determined using Yamane’s formula (1973). A five-point Likert scale questionnaire, validated by five experts in research and management, served as the primary data collection instrument, yielding a reliability coefficient of 0.97. Stratified sampling was employed to gather the data, which were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. Additionally, content analysis was used for the qualitative component. The findings revealed that the overall input of the system was rated at an Agree level, although limited budget allocation and the absence of research manuals were identified as critical issues. The research process was frequently practiced, but deficiencies in applying research findings were noted. The output was similarly rated at an Agree level, though there was limited utilization of research outcomes. While generally positive, feedback mechanisms lacked sufficient depth in reflection and improvement. To optimize research management, it is recommended that managers focus on securing financial resources, providing comprehensive research guides, enhancing the utilization of research outputs, and strengthening feedback processes